2019
DOI: 10.1177/0267659119830012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ex vivo extracorporeal membrane oxygenation flow dynamics on immune response

Abstract: Background: Extracorporeal membrane oxygenation is a life-saving support for heart and/or lung failure patients. Despite technological advancement, abnormal physiology persists and has been associated with subsequent adverse events. These include thrombosis, bleeding, systemic inflammatory response syndrome and infection. However, the underlying mechanisms are yet to be elucidated. We aimed to investigate whether the different flow dynamics of extracorporeal membrane oxygenation would alter immune responses, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…The latter creates an inflammatory reaction, as already reported in the systemic inflammatory response syndrome, that involves leukocytes, platelet endothelial cells, intrinsic and extrinsic coagulation, cytokines, and complement system [23]. The result is an unbalance between pro-coagulant and anticoagulant factors, e.g., fibrinogen contributes to thrombus formation, while loss of high molecular vWF causes a bleeding tendency [24].…”
Section: Cytokine Stormmentioning
confidence: 87%
“…The latter creates an inflammatory reaction, as already reported in the systemic inflammatory response syndrome, that involves leukocytes, platelet endothelial cells, intrinsic and extrinsic coagulation, cytokines, and complement system [23]. The result is an unbalance between pro-coagulant and anticoagulant factors, e.g., fibrinogen contributes to thrombus formation, while loss of high molecular vWF causes a bleeding tendency [24].…”
Section: Cytokine Stormmentioning
confidence: 87%
“…Even though strict anticoagulation are not definitely accepted, guidelines and experts opinion suggest the higher anticoagulation level to be used. [33][34][35][36][37] A flowchart of the literature review and screening is shown in Figure 1. The data were extracted from 16 articles.…”
Section: Methodsmentioning
confidence: 99%
“…[39][40][41][42] As soon as ECMO blood flow commences, plasmatic proteins (in particular, coagulation factors), fibrinogen, and von Willebrand factor (vWF) are consumed by the cleavage by the ADAMTS-13 protein. 37,43 Fibrinogen may contribute to thrombus formation, while loss of high-molecular vWF may contribute to a bleeding tendency. 44 Platelets can be activated by multiple mechanisms: contact with biomaterial interface causes exposure of surface integrins and adhesion to the circuit; high shear stress, due to blood flow through the pump and oxygenator, induces activation of surface proteins, spreading the process, and exposing the phospholipids.…”
Section: Pathophysiology Of Coagulation Activation During Ecmomentioning
confidence: 99%
“…reduction was reported by Adrian et al, this was not observed by Graulich et al and partially observed by Ki et al (32,33,37). The discrepancies between the outcomes could be rationalized by the utilization of different ECMO technology, model setup, and blood flow rates.…”
Section: (39)mentioning
confidence: 79%
“…In response to the continuous exposure to non-physiological conditions (e.g. flow rates and associated shear stress) and significant release of inflammatory mediators during ECMO (16,18,34,35,37,39,(65)(66)(67), cells of the endothelial lining are likely to convert into an activated state (68,69). This can subsequently elevate leukocyte adhesion [from phenotypic modulation (13,17,18,(34)(35)(36)] onto either the artificial surface of the ECMO circuit (23,24,70) or the endothelium itself (68,69), possibly acting as a consistent regulator of cell attachment in vivo.…”
Section: (39)mentioning
confidence: 99%